E-learning methodologies fundamentals, technologies and applications - Goyal, Mukta; Krishnamurthi, Rajalakshmi; Yadav, Divakar (IET computing series, 2021)
This book covers state of the art topics including user modeling for e-learning systems and cloud, IOT, and mobile-based frameworks. It also considers security challenges and ethical conduct using Blockchain technology